2012
DOI: 10.1063/1.4722642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AlN growth temperature on trap densities of in-situ metal-organic chemical vapor deposition grown AlN/AlGaN/GaN metal-insulator-semiconductor heterostructure field-effect transistors

Abstract: The trapping properties of in-situ metal-organic chemical vapor deposition (MOCVD) grown AlN/AlGaN/GaN metal-insulator-semiconductor heterostructure field-effect transistors (MIS-HFETs) with AlN layers grown at 600 and 700 °C has been quantitatively analyzed by frequency dependent parallel conductance technique. Both the devices exhibited two kinds of traps densities, due to AlN (DT-AlN) and AlGaN layers (DT-AlGaN) respectively. The MIS-HFET grown at 600 °C showed a minimum DT-AlN and DT-AlGaN of 1.1 x 1011 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…AlN has also been reported to help reduce current collapse [13]. There are two main methods used for the deposition of AlN namely metal-organic chemical vapor deposition [14] (MOCVD) and plasma-enhanced atomic layer deposition [15,16] (PEALD). However, the growth temperature of MOCVD (>600 • C) is not desirable for the fabrication of AlGaN/GaN HEMTs.…”
Section: Introductionmentioning
confidence: 99%
“…AlN has also been reported to help reduce current collapse [13]. There are two main methods used for the deposition of AlN namely metal-organic chemical vapor deposition [14] (MOCVD) and plasma-enhanced atomic layer deposition [15,16] (PEALD). However, the growth temperature of MOCVD (>600 • C) is not desirable for the fabrication of AlGaN/GaN HEMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations of the effects of oxidation on the surface structure and chemical bonding states of AlGaN/GaN heterostructures reveals that the density and distribution surface donor states depend on the condition of oxidation that was explained by the formation of two types of oxide structures providing different types of donor states . On the other hand, it was experimentally found that high‐density 2DEG forms in unoxidized heterostructures in situ passivated by different materials , therefore, the role of oxidation is not yet clarified.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the interface states in the AlN layer are not uniformly distributed [45]. A comparison between the minimum Dit values obtained in this study and the values using PEALD AlN [47], [100] and in-situ MOCVD AlN [106], [131] can be seen in Table 5.…”
Section: Device Fabrication -Mis-diode and Mishemtmentioning
confidence: 76%
“…Diamond symbols are single crystal samples measured by Slack et al [103] (in purple), and Rounds et al [104]. Square symbols are a poly-crystalline bulk sample [113] (in green) and various polycrystalline films (grey: Kuo et al [106], purple: Duquenne et al [105], black: Zhao et al [107], red:…”
Section: Table Of Contentsmentioning
confidence: 99%
See 1 more Smart Citation